Qualitative Research: Analysis of Factors Influencing the Utilization of ANC Services - Rahmah, Shinta; Agustina, Dewi; Astuty, Delfriana Ayu (Indonesian Journal of Global Health Research, 2024)
According to WHO, in 2020 MMR worldwide amounted to 295,000 deaths caused by many factors. In 2019-2020, MMR in Indonesia showed a significant increase of 4,197 cases to 4,627 cases. ANC services are health services carried out by health workers carried out in accordance with predetermined standards, aimed at monitoring the health of mothers and children. If ANC utilization services are not utilized properly, then many impacts will affect, for example, According to WHO, in 2020 MMR worldwide amounted to 295,000 deaths caused by many factors. In 2019-2020, MMR in Indonesia showed a significant increase of 4,197 cases to 4,627 cases. ANC services are health services carried out by health workers carried out in accordance with predetermined standards, aimed at monitoring the health of mothers and children. If ANC utilization services are not utilized properly, then many impacts will affect, for example, not being able to detect early health problems experienced. Objective: this study aims to analyze what factors influence the use of ANC services in pregnant women. This study uses exploratory qualitative research methods with centralized interviews also using secondary data from national articles using electronic media Google Scholar data base (2020-2023). MMR in Pematang Jaya sub-district is 0%, while K1 coverage is 81.34% and K4 is 87.31% in 2022. The most dominant factors are predisposing characteristics and reinforcing characteristics which include factors regarding the knowledge of pregnant women, attitudes of pregnant women and support from husbands and families, the role of posyandu cadres and village midwives. In this study, it can be concluded that antenatal care services at UPT Puskesmas Pematang Jaya have been carried out well. The influencing factors are in the predisposing characteristics that include maternal knowledge and maternal brushes and the reinforcing characteristics include the support factors of husbands and families as well as the village cadres and midwives who are doominan to influence ANC visits. not being able to detect early health problems experienced. Objective: this study aims to analyze what factors influence the use of ANC services in pregnant women. This study uses exploratory qualitative research methods with centralized interviews also using secondary data from national articles using electronic media Google Scholar data base. MMR in Pematang Jaya sub-district is 0%, while K1 coverage is 81.34% and K4 is 87.31% in 2022. The most dominant factors are predisposing characteristics and reinforcing characteristics which include factors regarding the knowledge of pregnant women, attitudes of pregnant women and support from husbands and families, the role of posyandu cadres and village midwives. In this study, it can be concluded that antenatal care services at UPT Puskesmas Pematang Jaya have been carried out well. The influencing factors are in the predisposing characteristics that include maternal knowledge and maternal brushes and the reinforcing characteristics include the support factors of husbands and families as well as the village cadres and midwives who are doominan to influence ANC visits